Limitações nutricionais para o colonião (Panicum maximum Jacq) e braquiária (Brachiaria decumbens Stapf) em latossolo da região noroeste do Estado do Paraná - Ferrari Neto, João (1991)
The gradual reduction of the support capacity of pasture in northwest region of Paraná State is due to reduction in soil fertility level triggered by erosion and inappropriate soil management. In order to recuperate the pasture it is common among farmers the cultivation of annual crops for one year. With the expansion of cassava cultivation in such a region, soil fertility level has decreased further due to the fact that farmer rarely fertilize this culture. As a consequence, it has been observed productivity reduction as well as nutritional value of the pasture and increase of invading plants. This study involve the cultivation in greenhouse of guinea grass (Panicum maximum Jacq) and braquiária grass (Brachiaria decurobens Stapf) in a Dark Red Latosol of the northwest region of Paraná State, with the objective of evaluating the effect of its fertility level upon growth and mineral nutrition of those pastures. Such evaluation was done through the lacking nutrient technic. The soil was unable to supply satisfactorily N, P, K and S to guinea grass and braquiária grass. On the other hand, there was no problem with regard to Ca, Mg and minor nutrients supplying capability. Also, liming showed to be desnecessary. Both forage had high content of Mn, antecipating problems with animal nutrition. Omission of N, P, K and S reduced growth of aerial part by 25, 25, 30 and 41%, respectively, as compared to complete treatment. Root growth, however, was most affected by lacking of K. Shooting of both species was affected in a decreased manner by lacking of P, N, S and K, being braquiária grass more prolific than guinea grass. Therefore, in such a soil the growth of both species will only be satisfactory with adequate supply of N, P, K and S. Braquiária grass had greater dry matter production and was more efficient in utilizing N, P, K and S than guinea grass. For the complete treatment, it was observed the following tendence of nutrient accumulation in the aerial part, considering both harvests: Braquiária grass: N > K > Ca > P > Mg > S > Mn > Fe > Zn > B > Cu; Guinea grass: N> K> P >Ca>Mg>S>Mn>Fe>Zn>B> Cu.